2012
DOI: 10.1161/hypertensionaha.112.197889
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium, Thiazides, Aldosterone, and Mineralocorticoid Receptors

Abstract: Alderman et al 1 on the clinical significance of hypokalemia and hyperkalemia in the antihypertensive treatment and prevention of cardiovascular complications. The conclusion was that, in most patients, concerns about potassium levels should not influence the clinician's decision about initiating hypertension treatment with low-moderate doses of thiazides. Chlorthalidone reduces the risk of congestive heart failure, in comparison with lisinopril and amlodipine, 1 but it also activates the renin-angiotensinaldo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The authors reported a significant reduction of the prevalence of heart failure relapse and cardio-cerebrovascular accidents when the MR blockers were added to the conventional treatments of these pathological conditions (1820). The protective effect of MR blockers is opposite to the effect of other diuretics that increase aldosterone secretion and inflammatory reaction (21, 22). Recent researches are exploring the protective effect of spironolactone as an anti-inflammatory and immunomodulatory agent even in the treatment of other pathological conditions, such as rheumatoid arthritis and central serous chorioretinopathy (23, 24).…”
Section: Mineralocorticoids Licorice and Inflammationmentioning
confidence: 99%
“…The authors reported a significant reduction of the prevalence of heart failure relapse and cardio-cerebrovascular accidents when the MR blockers were added to the conventional treatments of these pathological conditions (1820). The protective effect of MR blockers is opposite to the effect of other diuretics that increase aldosterone secretion and inflammatory reaction (21, 22). Recent researches are exploring the protective effect of spironolactone as an anti-inflammatory and immunomodulatory agent even in the treatment of other pathological conditions, such as rheumatoid arthritis and central serous chorioretinopathy (23, 24).…”
Section: Mineralocorticoids Licorice and Inflammationmentioning
confidence: 99%
“…The only clinical situations associated with an increase in mineralocorticoids and volume expansion are primary aldosteronism and pseudohyperaldosteronism . The inflammatory effect of aldosterone is also evident in patients treated with thiazides and amiloride, while aldosterone receptor blockers are able to prevent cardiovascular risk . Thiazides and furosemide can reduce blood pressure but they increase aldosterone, and mineralocorticoid receptors are not blocked as occurs with spironolactone derivatives.…”
Section: Homeostatic Equilibrium Of Sodium and Watermentioning
confidence: 99%
“…Several studies have now demonstrated that a significant incidence of ventricular ectopic activity with diuretic-induced hypokalemia is responsible for sudden death [ 4 ]. Apart from plasma potassium levels associated with thiazides, the activation of the renin-angiotensin-aldosterone system and, in particular, the stimulation of mineralocorticoid receptors are key determinants in the inflammatory process and the progression of cardiovascular disease [ 5 ].…”
Section: Introductionmentioning
confidence: 99%